PERSEPSI MANFAAT DAN PERILAKU NASABAH TERHADAP BANK SYARIAH - Kurniawan, Fery; Fasa, M Iqbal; Suharto, Suharto (STAI Darul Qalam Tangerang, 2024)
Islam has regulated human behavior in meeting their needs, namely not deviating from Islamic teachings, including financial institutions. Islamic banks are now popular among the people of Indonesia so that Islamic banks have a big role in improving the banking world in Indonesia. With a population of Indonesia that is more Muslim, Islamic banks have great prospects with increased and knowledge about the awareness to use Islamic banking products and feel the benefits. However, different reactions will describe different behaviors, namely different consumers will give different reactions in terms of feelings towards information about the existence of Islamic banking, attitudes usually play a major role in shaping behavior. The purpose of this study was to determine the effect of knowledge and attitudes on people's behavior in Islamic banks.